THE EFFECT OF SPECIFIC COMPLEX TRAINING ON IPPON-SEOINAGE THROWING PERFORMANCE IN JUDO PLAYERS - Younghattee , Juthamas; Srihirun, Kanang (Journal of Sports Science and Health, 2023)
Purpose: this study aimed to investigate the effect of specific complex training on ippon-seoinage throwing performance in judo players. Methods: eighteen male judo players from University, Aged 18-24 years were recruited to participate in this study. The participants were randomly assigned into 2 groups (n=9/each group). In the experimental group, the participants underwent specific complex training program, consisted of 6 thrusters exercise at 85%1RM and then continue 12 wood chops with medicine ball at 10% of body weight. The control group performed a normal complex training program, perform 6 squat exercise at 85%1RM and then continue 12 squat jumps. Both groups perform 4 sets of training day twice a week for 6 weeks in addition to their normal. Before and after 6-week of training, throwing velocity, muscular power, and muscular strength were determined. Data were analyzed using dependent and independent samples t-test to determine the statistical significance level at p- value <.05. Results: after six weeks of training, muscular strength and muscular power were significantly greater (P<0.05) in both group. Moreover, throwing velocity in experimental group was a significantly higher (P<0.05) after training and significantly greater (P<0.05) than control group at post-exercise. Conclusion: the specific complex training program is more effective for improving throwing performance in judo players.